Modification of a limestone solubility method and potential to correlate with in vivo limestone calcium digestibility. (8th August 2019) - Kim, S-W; Li, W; Angel, R; Plumstead, P W
ABSTRACT: Work was done to modify a limestone solubility assay to improve predictions of in vivo apparent ileal digestibility of Ca (AID Ca ) in broilers and impacts on AID P. Limestones (LIME ) were obtained from 3 commercial sources. LIME-1 (0.633 mm mean diameter, GMD ); LIME-2 (ground sub-sample of LIME-1, GMD = 0.063 mm); LIME-3 (GMD = 0.326 mm), and LIME-4 (GMD = 0.831 mm). Solubility was determined at 5, 15, and 30 min of incubation using either a 0.2 N HCl (S1 ) or a pH 3 HCl (pH = 0.26) solution buffered with 3 M glycine (S2 ) to mimic gizzard and proventriculus pH. An AID trial was conducted with 320 Ross 708 male broilers. Treatments (Trt ) were no added LIME, or added LIME-1, 2, 3, and 4 to achieve 0.67% Ca, to a basal diet (no added inorganic P, 0.07% Ca) with or without 1, 000 U phytase/kg (36 h, 23 to 24 D of age, n = 8, 4 birds/n). Distal ileal digesta was collected from all birds and pooled by pen. Irrespective of interaction, LIME solubilized quicker and more completely with S1 vs. S2 at all time points ( P < 0.05). LIME-2 solubilized the quickest, while LIME-3 had the lowest solubility through all incubation times ( P < 0.05). The AID Ca was 66.30, 47.46, 19.93, and 66.33% for LIME-1, 2, 3, and 4, respectively (0 U/kg, P < 0.05). Phytase inclusion increased AID Ca by 15% on average ( P < 0.05). The AID P dig was highest in no LIME added diet (74.91%) and adding LIME reduced ( P < 0.05) AID P to 23.14, 12.78, 65.47, and 37.40%, for LIME-1, 2, 3, and 4, respectively in the absence of phytase. Regression showed that GMD, 15- and 30-min solubility were critical for AID Ca (R 2 between 0.978 and 0.988). In conclusion, the solubility dynamics including speed and extend of solubilization, rather than a single timepoint, yield better predictions for in vivo Ca digestibility of LIME.